Psychological Birth Order and Achievement Goal Orientation of High School Students engaged in Shadow Education - Cayubit, Ryan Francis O.; Ligot, Nestlhyn B; Lim, Jamie Therese T; Malaluan, Inah Karla R; Managbanag, Erika Mae U; Quindoza, Gretchen Hazelle D (UI Scholars Hub, 2021)
The focus of the current study is to examine the nature of the relationship of goal orientation with psychological birth order. Likewise, it also looked into the ability of psychological birth order to influence the endorsement of achievement goals (mastery-approach and avoidance; performance- approach and avoidance). A total of 220 high school students engaged in shadow education answered the White-Campbell Psychological Birth Order Inventory (PBOI) and the Achievement Goal Questionnaire (AGQ). Based on the regression analysis performed, only the pairing of psychological birth order and performance-approach is significant while those of psychological birth order, mastery-approach, mastery-avoidance, and performance-avoidance are not significant. Further analysis revealed that those who are psychologically firstborns tend to endorse the mastery-approach goal orientation while those who are psychologically youngest or lastborn endorses mastery-avoidance.